2020
DOI: 10.1183/13993003.03481-2020
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary recovery after COVID-19: an observational prospective multicentre trial

Abstract: BackgroundAfter the 2002/2003 SARS outbreak, 30% of survivors exhibited persisting structural pulmonary abnormalities. The long-term pulmonary sequelae of coronavirus disease 2019 (COVID-19) are yet unknown, and comprehensive clinical follow-up data are lacking.MethodsIn this prospective, multicentre, observational study, we systematically evaluated the cardiopulmonary damage in subjects recovering from COVID-19 at 60 and 100 days after confirmed diagnosis. We conducted a detailed questionnaire, clinical exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
427
1
37

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 366 publications
(524 citation statements)
references
References 32 publications
29
427
1
37
Order By: Relevance
“… 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 Overall, 7 studies were conducted in China 12 , 22 , 26 , 27 , 36 , 51 , 52 ; 6 each in the United Kingdom 9 , 15 , 21 , 28 , 32 , 37 and Spain…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 Overall, 7 studies were conducted in China 12 , 22 , 26 , 27 , 36 , 51 , 52 ; 6 each in the United Kingdom 9 , 15 , 21 , 28 , 32 , 37 and Spain…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-three studies recruited only inpatients; 10 studies 11 , 13 , 29 , 34 , 35 , 40 , 41 , 45 , 47 , 48 included a combination of outpatients and inpatients, with the proportion of inpatients ranging from 23.0% to 80.0% ( Table 1 ), and 2 studies 24 , 33 included only outpatients. Three studies excluded patients who were unable or unwilling to receive a magnetic resonance imaging scan.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonnweber's research evaluated data on 145 patients with COVID-19 at 60 and 100 days after confirmed diagnosis, and found that 41% of all subjects exhibited persistent symptoms 100 days after COVID-19 onset, with dyspnea being most frequent (36%). Accordingly, patients still displayed an impaired lung function, with a reduced diffusing capacity in 21% of the cohort being the most prominent finding (28). In our study, after two weeks of PR, the patients' mMRC score and oxygen intake decreased and SpO 2 increased significantly.…”
Section: Discussionmentioning
confidence: 44%
“…In line, radiological signs of fibrosis become apparent as early as 3 weeks after diagnosis (169) and persist over months (170,171). After 3 months, impaired diffusion capacity and persisting radiological abnormalities are observed in many survivors, while others recover completely (172)(173)(174)(175)(176). Further studies are ongoing whether radiological and functional impairments are chronic and even progressing.…”
Section: Emerging Evidence Of Covid-19-associated Lung Fibrosismentioning
confidence: 93%